Nutritional composition,antioxidants and antimicrobial activities in muscle tissues of mud crab,Scylla paramamosain - Wan Roslina, Wan Yusof; Noorasmin, Mokhtar Ahmad; Mohd Alhafiizh, Zailani; Mardhiah, Mohd Shahabuddin; Ngieng, Ngui Sing; Awang Ahmad Sallehin, Awang Husaini (World Research Association, 2020)
Mud crab, Scylla paramamosain known as a green mud crab, has become a popular seafood due to its meat quality. In addition, this marine invertebrate has been found to possess peptides with different biological activities and potentials. The aim was, first, to determine the basic nutritional content and second, to screen for the antioxidants and antimicrobials activities in the tissue of mud crab, S. paramamosain. Percentages of carbohydrate, protein and fat in S. paramamosain were 2.32%, 12.53% and 0.23% respectively. The IC50 of methanol extract of tissue S.paramamosain in DPPH scavenging assay was found to be 1.79±0.0 mg/mL. Moreover, superoxide dismutase (SOD) activity was measured as percentage inhibition by SOD was found to be 88.7% ± 2.2, followed by catalase (CAT) activity which was 44.3 ± 2.9 µmol of hydrogen peroxide (H2O2) per minute respectively.The total glutathione (GSH) in the tissues extract was 0.5 µg/mL. In antimicrobial assay, the methanolic extract of S. paramamosain revealed its potential as antimicrobial agents against three human clinical pathogens with minimal inhibitory concentration (MIC) values ranging between 7 to 62 µg/mL. Minimal bactericidal concentration (MBC) values were higher than 125 µg/mL. The study reported that muscle tissues of S. paramamosain are enriched with high protein content and possess antioxidant and antimicrobial activities. Therefore, further studies are needed to identify and isolate the bioactive compounds in the tissue extracts of S. paramamosain to add more values and potentials of mud crabs.